2021
DOI: 10.24891/fc.27.10.2197
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effectiveness of regulation of inter-budgetary relations in the Russian Federation constituent entities in conditions of instability

Abstract: Subject. This article considers the peculiarities of regulation of inter-budgetary relations in the constituent entities of the Russian Federation in the conditions of an unstable economic situation. Objectives. The article aims to form an approach to assessing the effectiveness of the distribution of transfers from regional budgets in current conditions. Methods. For the study, we used the methods of analysis and synthesis, analogy, comparison, and grouping. Results. The article offers recommendations for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This means overcoming the traditional view of intergovernmental budgetary regulation as an auxiliary process that ensures the transfer of funds between budgets at different levels. It can be concluded that any relationship between state authorities and municipalities arising from the distribution of tax revenues, spending powers, and especially transfers, affects the interests of both parties and presupposes their harmonization [5].…”
Section: Administrativementioning
confidence: 99%
“…This means overcoming the traditional view of intergovernmental budgetary regulation as an auxiliary process that ensures the transfer of funds between budgets at different levels. It can be concluded that any relationship between state authorities and municipalities arising from the distribution of tax revenues, spending powers, and especially transfers, affects the interests of both parties and presupposes their harmonization [5].…”
Section: Administrativementioning
confidence: 99%